2015
DOI: 10.1186/s12889-016-2702-0
|View full text |Cite
|
Sign up to set email alerts
|

Predicting condom use in adolescents: a test of three socio-cognitive models using a structural equation modeling approach

Abstract: BackgroundThe theory of planned behavior (TPB), socio-cognitive model (SCM), and information-motivation-behavioral skills (IMB) model are effective in predicting condom use. However, the adequacy of these three theoretical models in predicting the frequency of condom use (FCU) among young people has not been compared. This cross-sectional study tested the applicability and suitability of these three models in predicting the FCU, and analyzed the relationships among the postulated constructs.MethodsSexually exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
59
0
12

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 73 publications
(77 citation statements)
references
References 57 publications
6
59
0
12
Order By: Relevance
“…En consecuencia, sería esperable que los adolescentes que recibieron la intervención presentaran mayor probabilidad de usar el preservativo en sus relaciones sexuales, puesto que presentan mayor nivel de conocimientos sobre el VIH y los métodos de protección, y una actitud más favorable hacia el uso del preservativo que los miembros del grupo control. Un reciente estudio empírico pone a prueba tres modelos socio-cognitivos de salud -la TAP (Ajzen, 1991;Fishbein & Ajzen, 2011), el IMH (Fisher & Fisher, 1992;Fisher et al, 1996;Fisher et al, 2002;Fisher, Fisher, & Shuper, 2009) y el MSC de Bandura (1977;1986;1994) para identificar las variables mediadoras de la eficacia de COMPAS (frente a un grupo control) para predecir el uso del preservativo en adolescentes escolarizados tras dos años de su aplicación (Espada, Morales, Guillén-Riquelme, Ballester, & Orgilés, 2016). De acuerdo con este estudio español de corte longitudinal, en el que participaron 410 adolescentes sexualmente activos entre 13-18 años, tener una actitud favorable hacia el uso del preservativo en el postest fue uno de los principales predictores de la intención de usar el preservativo a los 12 meses, y del uso del preservativo a los 24 meses de recibir el programa.…”
Section: Discussionunclassified
“…En consecuencia, sería esperable que los adolescentes que recibieron la intervención presentaran mayor probabilidad de usar el preservativo en sus relaciones sexuales, puesto que presentan mayor nivel de conocimientos sobre el VIH y los métodos de protección, y una actitud más favorable hacia el uso del preservativo que los miembros del grupo control. Un reciente estudio empírico pone a prueba tres modelos socio-cognitivos de salud -la TAP (Ajzen, 1991;Fishbein & Ajzen, 2011), el IMH (Fisher & Fisher, 1992;Fisher et al, 1996;Fisher et al, 2002;Fisher, Fisher, & Shuper, 2009) y el MSC de Bandura (1977;1986;1994) para identificar las variables mediadoras de la eficacia de COMPAS (frente a un grupo control) para predecir el uso del preservativo en adolescentes escolarizados tras dos años de su aplicación (Espada, Morales, Guillén-Riquelme, Ballester, & Orgilés, 2016). De acuerdo con este estudio español de corte longitudinal, en el que participaron 410 adolescentes sexualmente activos entre 13-18 años, tener una actitud favorable hacia el uso del preservativo en el postest fue uno de los principales predictores de la intención de usar el preservativo a los 12 meses, y del uso del preservativo a los 24 meses de recibir el programa.…”
Section: Discussionunclassified
“…Hasil penelitian ini juga didukung oleh penelitian yang dilakukan James dan Abieyuwa (2013) bahwa sikap seorang remaja putri untuk melakukan perilaku seksual tidak aman berpeng-aruh terhadap perilaku seksual tidak aman dari remaja putri. Espada et al (2016) menyebutkan bahwa sikap remaja berpengaruh terhadap niat remaja untuk berperilaku seksual aman. Hal senada juga disampaikan oleh Scalco et al (2017) bahwa sikap adalah salah satu faktor yang mempengaruhi perilaku individu, semakin kuat sikap positif individu untuk melakukan semakin kuat niat individu tersebut untuk melakukan perilaku tertentu tersebut.…”
Section: Hasil Analisis Multilevelunclassified
“…Hasil penelitian ini sejalan dengan penelitian Espada et al (2016) bahwa persepsi kontrol perilaku remaja berpengaruh terhadap perilaku seksual aman. Persepsi kontrol perilaku memegang peranan penting dalam perilaku seseorang.…”
Section: Hubungan Persepsi Kontrol Perilaku Dengan Perilaku Seksual Aunclassified
See 1 more Smart Citation
“…Nevertheless, the positive impact of PBC is not consistent among literature. More recently, Espada et al (2016) compared TPB and IMB in their effi cacy to predict condom and observed that PBC has had no eff ect in predicting frequency of condom use and has pointed to the importance to test integrative models that include personal, contextual, environmental and social factors. Visser and Smith (2001) observed that for those who sometimes use a condom, the most important determinants were the characteristics of the interaction between the sexual partners and the state-like characteristics of the individuals concerned.…”
mentioning
confidence: 99%